Models Supported Transfer of Learning to the Workplace - Zainon, Mat Sharif; Syed Nurulakla, Syed Abdullah; Mohd Yusof, Mardic (2014)
This paper presents a critical review on training transfer models, a comparison between 10 training transfer models including the author’s study model. The objective of this paper is to provide a critical review on training transfer models and the theoretical implication of training transfer model. In conclusion, the measurement of transfer of training should be inclusive of environment, training related and motivational factors.